The impact of psychiatric and extraintestinal comorbidity on quality of life and bowel symptom burden in functional GI disorders. Issue 9 (29th July 2014) - Vu, J.; Kushnir, V.; Cassell, B.; Gyawali, C. P.; Sayuk, G. S.
Abstract Background Functional gastrointestinal disorders (FGID) patients report poor health‐related quality of life (HRQOL) and experience high rates of psychiatric and extraintestinal functional disorder (EIFD) comorbidity. The independent influence of these comorbidities on HRQOL and symptom burden remains unknown. We sought to determine whether FGID with mood or EIFD comorbidity have poorer HRQOL and greater GI symptom burdens; to determine the influence of comorbidities on HRQOL in FGID independent of bowel symptoms. Methods Subjects reported on comorbidities (anxiety, depression, somatization, EIFD), FGID criteria (irritable bowel syndrome, IBS; functional dyspepsia, FD) using ROME III Research questionnaire, GI symptom burden, and HRQOL. Differences in measures were assessed between subjects with and without ROME III criteria. Multiple regression determined the relative contribution of comorbidities to HRQOL, and mediation analysis explored whether comorbidity influences HRQOL. Key Results In a cohort of 912 GI outpatients (47.2 ± 1.5 years, 75.8% female), 606 (66.4%) met Rome III IBS and/or FD criteria. Comorbidities were common in FGID (≥1 in 77.4%), leading to lower HRQOL and greater GI symptom burden (each p < 0.05). Poorer HRQOL was predicted by both psychiatric and EIFD comorbidity (each p < 0.05) independent of GI symptoms (p < 0.001). Comorbidities together exerted a greater effect on predicted variation in HRQOL (70.9%) relative to GI symptoms (26.5%). Conclusions & Inferences Psychiatric and EIFD comorbidities are common in FGID, decrease HRQOL and are associated with greater GI symptom burdens; these factors were stronger predictors of HRQOL than GI symptoms in FGID patients.